Mata Pencaharian Berkelanjutan Kondisi Masyarakat Adat Lekuk 50 Tumbi Dan Peran Lembaga Adat - Izzurrahman, Muhamamd Hasan; Nasri, Muhammad Azami (UI Scholars Hub, 2023)
Sustainable livelihoods are key for communities to sustain their lives. However, limited access to and utilisation of natural resources, particularly customary forests, has led to a decline in the livelihoods of the Lekuk 50 Tumbi indigenous community. Difficulty in clearing land is a major obstacle for them in finding alternative income. This research aims to evaluate the quality of life of the Lekuk 50 Tumbi indigenous community with a focus on indigenous institutions' initiatives based on sustainable livelihoods, considering the five aspects of capital. Through in-depth interviews and qualitative analysis, natural capital, physical capital, human capital, financial capital and social capital in the study area were evaluated. The findings show that all five capitals are sustainable in the context of the Lekuk 50 Tumbi indigenous community. The role of customary institutions is recognised as a key factor in maintaining the sustainability of community livelihoods, despite constraints in access and utilisation of available natural resources. The research illustrates the urgency of supporting customary institutions in maintaining sustainable livelihoods and addressing the challenges faced by the Lekuk 50 Tumbi indigenous community.